Perubahan Benteng Oranje di Ternate – Maluku Utara (Abad XVII-XX) - Suwindiatrini, Komang Ayu; Nayati, Widya (JANUS, 2024)
The Indonesian archipelago has been known for centuries as a source of spices that are favored in many countries. The desire to obtain these spices from the first source has brought Europeans to the islands since 15th century. They sent their maritime fleets to establish trading posts in the archipelago, especially in Maluku which was rich in nutmeg and cloves. One of the archaeological remains that serves as evidence of the presence and control of Europeans, especially the Dutch, in this area is the existence of Fort Oranje in Ternate. However, there is not much of the historical background on the development of Fort Oranje has been revealed so far. This paper attempts to fill the dearth of information about the fort. The study was conducted by identifying the attributes shown in at least five drawings and plans of the Fort, which were then combined with existing historical data. The results showed that there were several changes in the form, function and role of Fort Oranje from the beginning of its establishment to the present. The reasons for these changes are mainly due to the needs of the Dutch communities who lived in the fort as well as the changing political and security condition throughout its history. Another contributing factor is government policy both during the colonial period and after Indonesia's independence. Due to the limited amount of visual data to reconstruct the long development, only a few stages of Fort Oranje transformation can be revealed. === Selama berabad-abad, kepulauan Indonesia telah dikenal sebagai sumber rempah yang digemari di banyak negara. Keinginan untuk mendapatkan rempah-rempah ini dari sumber pertama telah membawa bangsa Eropa ke kepulauan ini sejak akhir abad ke-15. Mereka mengirimkan armada lautnya untuk mendirikan pos-pos perdagangan di Nusantara, terutama di Maluku yang kaya akan pala dan cengkeh. Salah satu peninggalan arkeologi yang menjadi bukti kehadiran dan penguasaan bangsa Eropa, khususnya Belanda, di kepulauan rempah-rempah ini adalah keberadaan Benteng Oranje di Ternate. Namun, sejauh ini belum banyak latar belakang sejarah perkembangan Benteng Oranje yang terungkap. Tulisan ini mencoba mengisi kelangkaan informasi mengenai benteng tersebut dengan menyajikan hasil kajian terhadap data visual Benteng Oranje berupa gambar dan denah lama yang masih dapat diakses. Kajian dilakukan dengan mengidentifikasi atribut-atribut yang ditunjukkan pada setidaknya lima gambar dan denah benteng, yang kemudian dipadukan dengan data sejarah historis yang ada. Hasil penelitian menunjukkan bahwa terdapat beberapa perubahan bentuk, fungsi dan peran Benteng Oranje dari awal berdirinya hingga saat ini. Penyebab perubahan tersebut terutama disebabkan oleh perubahan kebutuhan masyarakat Belanda yang tinggal di dalam benteng serta situasi politik dan keamanan yang terus berubah sepanjang sejarahnya. Faktor lain yang turut berperan adalah kebijakan pemerintah baik selama masa kolonial maupun setelah kemerdekaan Indonesia.